Sulzbacheromyces yunnanensis, a new record for Thailand - Nakarin Suwannarach (2019)
© 2019 Mycotaxon Ltd. All rights reserved. Specimens of a clavarioid basidiolichen collected in Thailand were identified as Sulzbacheromyces yunnanensis, based on morphology and similarities of ITS genes. A full description and illustration are provided. This is the first record of S. yunnanensis from Thailand.